The study of negotiation activities in foreign studies - Vahnina V.V. (Психология и право, 2016)
The article is devoted to the problem of studying the negotiation activities of foreign scientists. There are different trends in the study of negotiations law enforcement officers in crisis situations and the possibilities of overcoming and prevention of crisis negotiations. The author explores the different approaches of foreign scientists to the problem of negotiation in crisis situations involving the Commission of a crime. The author particularly notes the work of Slovak researchers who formed the Bank crises and analyzed the possibilities of overcoming the crisis conditions of the negotiation activities. In the article the results of research activities of scientists not only theorists but also practitioners. The leaders of the special units involved in the liberation of hostages, analyze the causes of crisis negotiations and the possibility of its overcoming. The analysis of the presented approaches allows foreign scientists to develop the concept of anti-crisis talks of employees of internal Affairs bodies and the perpetrators (the perpetrators of) criminal acts.